2022
DOI: 10.1029/2021jb022878
|View full text |Cite
|
Sign up to set email alerts
|

Time‐Lapse Record of an Earthquake in the Dry Felsic Lower Continental Crust Preserved in a Pseudotachylyte‐Bearing Fault

Abstract: Earthquakes recorded in the lower continental crust present a major conundrum with regard to rock mechanics and earthquake mechanisms because they occur well below the depth of the usual frictional to viscous (or brittle to ductile) transition. The properties and mechanical processes of these lower crustal earthquakes have generally been inferred from geophysical data, from laboratory experiments, or from analytical and numerical models. Complementary information comes from the study of exhumed rocks and in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 132 publications
1
14
0
Order By: Relevance
“…Recently, Dunkel et al 16 reported textures indicative of seismic faulting in dry lower crustal rocks from the Lofoten Archipelago in the Northern Norwegian Caledonides, indicating very high (≥1 GPa) stress levels and therefore suggesting that the lower crust was strong, not weak 17 . Similar suggestions have been made also for other field areas where dry, lower-crustal lithologies occur 18,19 . For the Bergen Arcs of Western Norway, such high stress levels were recently demonstrated directly by the presence of highly overpressured frictional melts along lower crustal faults 20 .…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Recently, Dunkel et al 16 reported textures indicative of seismic faulting in dry lower crustal rocks from the Lofoten Archipelago in the Northern Norwegian Caledonides, indicating very high (≥1 GPa) stress levels and therefore suggesting that the lower crust was strong, not weak 17 . Similar suggestions have been made also for other field areas where dry, lower-crustal lithologies occur 18,19 . For the Bergen Arcs of Western Norway, such high stress levels were recently demonstrated directly by the presence of highly overpressured frictional melts along lower crustal faults 20 .…”
supporting
confidence: 85%
“…With ongoing deformation, stresses build up until the yield stress is reached. Field observations demonstrate that this is followed by dynamic rupturing and highly localized seismic slip 19,39 . Associated wall rock damage allows fluid infiltration, metamorphic hydration reaction, and mechanical weakening of a 0.1-1 m wide zone of wall rocks 8 .…”
Section: Resultsmentioning
confidence: 99%
“…Interpretations of pulverization of single grains have recently accumulated from microstructural studies of lower crustal earthquakes in both naturally and experimentally deformed rocks (Austrheim et al., 2017; Incel et al., 2019; Petley‐Ragan et al., 2019; B. R. Song et al., 2020; Soda & Okudaira, 2018). Minerals observed to undergo pulverization‐style fragmentation include plagioclase (Pittarello et al., 2008; Soda & Okudaira, 2018; B. R. Song et al., 2020), garnet (Austrheim et al., 2017; Incel et al., 2019; Manktelow et al., 2022; Petley‐Ragan et al., 2019; B. R. Song et al., 2020) and diopside (Petley‐Ragan et al., 2019). In the Nusfjord samples, orthopyroxene is the only mineral to show microstructures compatible with pulverization style fragmentation, although on a centimeter‐scale the wider anorthosite is intensely fractured in places.…”
Section: Discussionmentioning
confidence: 99%
“…Such stress magnitudes prior to rupture have been implied by field characterization of pseudotachylyte‐bearing faults (Campbell et al., 2020) and, perhaps more commonly, are also associated with deformation linked to coseismic loading once rupture propagation has initiated (e.g., Anderson et al., 2021). This microstructural record of progressive and transient stress variation throughout the earthquake cycle (Anderson et al., 2021; Bestmann et al., 2012; Brückner & Trepmann, 2021; Campbell & Menegon, 2019; Johnson et al., 2021; Mancktelow et al., 2022; Petley‐Ragan et al., 2019) offers an under‐explored opportunity to further constrain deformation mechanisms and conditions associated with both prerupture stress amplification and coseismic rupture within the lower crust.…”
Section: Introductionmentioning
confidence: 99%
“…Under lower crustal conditions, most rock-forming minerals such as quartz and feldspars deform by ductile creep, which can obscure microstructures associated with seismic events (Kirkpatrick and Rowe, 2013). Garnet, notably, is considered mechanically and chemically stable under elevated temperatures and commonly preserves microstructures related to seismicity (e.g., Mancktelow et al, 2022;Trepmann and Stöckhert, 2002). Although garnet is not the most predominant mineral in the lower crust, it becomes increasingly important with depth constituting a large modal proportion in metamorphosed rocks (up to 50%; Villaseca et al, 1999) and is assumed to play a significant role in crustal strengthening (e.g., Ingrin and Madon, 1995;Jin et al, 2001;Ji et al, 2003).…”
Section: Introductionmentioning
confidence: 99%